Cystic brain metastases radiologically simulating neurocysticercosis - Troiani, Charlene; Lopes, Carla Cristina Barbosa; Scardovelli, Carlos Antônio; Nai, Gisele Alborghetti (São Paulo Medical Journal, 2011)
CONTEXT: Brain metastases are common complications of cancer. Magnetic resonance imaging (MRI), the main diagnostic imaging method in these cases, rarely shows cystic images. CASE REPORT: The patient was a 45-year-old woman who had had severe headache for a month that was refractory to medication, and had previously had breast cancer, which had been treated. The MRI showed the criteria for neurocysticercosis. Since there was no improvement with clinical treatment, we chose to excise the lesions. Histopathological analysis showed an epithelioid malignant neoplasm. CONCLUSION: From immunohistochemical analysis, it was concluded that this was a metastasis of breast carcinoma. Even when the MRI is not characteristic of cerebral metastasis, this hypothesis needs to be ruled out in patients with a previous history of cancer.